2008
DOI: 10.3139/146.101741
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and acoustic damage analysis and finite element stress simulation of air plasma-sprayed thermal barrier coatings under thermal cycling

Abstract: Degradation evolution and failure mechanisms of air plasma-sprayed thermal barrier coatings during thermal cycling were investigated using microstructural and acoustic emission analysis. The microcrack evolution observed suggests that the life-time is governed by the kinetics of crack formation, growth and linking of individual cracks. The damage in the thermal barrier coatings mainly occurs during cooling due to thermal-expansion mismatch stresses at the metal – ceramic interface. The effect of the minimum cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The delamination failure occurred after 2432, 1827 and 670 cycles, respectively. The lifetimes as a function of T min and T max for the high temperature dwell times of 2 hours and 20 minutes, respectively, are summarized in Acoustic emission analysis applied in situ during thermal cycling in temperature range 60-1050°C, as reported in [8], proved that damage occurred during cooling at temperatures below the ductile-to-brittle transition temperature of the BC due to an increase in thermally induced stresses at the TBC/BC interface. With decreasing temperature range of the thermal cycle (increase of minimum temperature) thermal stresses contribute less to TBC degradation compared to the 02001-p. 3 thermally activated damage processes, especially TGO growth.…”
Section: Thermal Cyclingmentioning
confidence: 96%
“…The delamination failure occurred after 2432, 1827 and 670 cycles, respectively. The lifetimes as a function of T min and T max for the high temperature dwell times of 2 hours and 20 minutes, respectively, are summarized in Acoustic emission analysis applied in situ during thermal cycling in temperature range 60-1050°C, as reported in [8], proved that damage occurred during cooling at temperatures below the ductile-to-brittle transition temperature of the BC due to an increase in thermally induced stresses at the TBC/BC interface. With decreasing temperature range of the thermal cycle (increase of minimum temperature) thermal stresses contribute less to TBC degradation compared to the 02001-p. 3 thermally activated damage processes, especially TGO growth.…”
Section: Thermal Cyclingmentioning
confidence: 96%
“…Yang et al performed the wavelet transform of AE signals to study the failure process of TBCs under tension [16] . Trunova et al reported the degradation evolution and failure mechanisms of APS TBCs during thermal cycling based on the analysis of microstructures and AE signals [17] . However, there are few works on the relationships between characteristic frequency spectrums of AE signals and fracture mechanisms of TBCs.…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that the number of specimens tested on the Caldecast XL 135 plate was limited, just one from each geometry. Even so, the cooling rate may not be the determining factor for TCF life; Trunova et al [15] found, for example, that the minimum temperature during cooling had a greater influence on life than the cooling rate. It should also be mentioned that the through-thickness temperature gradient in the specimens may be different between the rigs.…”
Section: Resultsmentioning
confidence: 99%